The dividend policy of capital groups and other dividend companies listed on the Warsaw Stock Exchange − research results - Jabłoński, Bartłomiej (Polityka dywidend grup kapitałowych oraz innych podmiotów notowanych na Giełdzie Papierów Wartościowych w Warszawie – wyniki badań, 2021)
The aim of the article was to present research on the characteristics of the dividend policy of capital groups and other dividend companies listed on the Warsaw Stock Exchange that paid dividends in 2012-2019 and to undertake a critical evaluation. The research relates to the methods of describing the dividend policy implemented by companies listed on the Warsaw Stock Exchange, which publish consolidated financial statements (capital groups) and measures of the system of payout of dividends by these entities. Based on the conducted research, it should be stated that capital groups are of a higher average annual dividend growth rate than companies publishing only separate financial statements, whilst the latter boast a higher average cumulative rate of dividends. The conducted research shows that the parent companies do not show whether they receive dividends from their subsidiary companies. However, based on the Spearman’s Rho analysis and the Pearson linear correlation coefficient for the analysed companies, it was found that there was a statistically significant link for capital groups and other companies between the average annual rate of return and the cumulative rate of dividends, and only for the remaining companies, a positive link between the average annual dividend growth rate and the cumulative rate of dividends (yet, this has not been confirmed by the Pearson’s linear correlation coefficient). The added value and application value are recommendations regarding the attractiveness of investing in dividend companies – capital groups or companies without related entities
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 1, s. 1-21
Keywords: capital group; dividend policy; determinants of dividend policy; Spearman's rank correlation coefficient; grupa kapitałowa; polityka dywidend; determinanty polityki dywidend; współczynnik korelacji rang Spearmana